International supply chain management. Lecture notes - Shyriaieva, N. V.; Makarenko, Anastasiya B.; Bilotserkivskyi, Oleksandr (My University, 2020)
The lectures cover foundations of the International Supply Chain Management course, including the role of logistics in economy and management, supply chain management, material flow management, supply, transportation, order processing and information systems, inventory management, warehousing, cargo handling, customer service. Questions for independent study are included. The lectures are developed for students of 073 "Management", 076 "Entrepreneurship, trade and exchange activity" majors.

Текст лекцій містить теоретичні засади курсу "Міжнародна логістика", включаючи роль логістики в економіці та менеджменті, управління ланцюгами поставок, управління матеріальним потоком, постачання, транспортування, системи обробки замовлень та інформаційні системи, управління запасами, складування, вантажопереробка, обслуговування споживачів. Наведено запитання для самостійної роботи студентів. Розраховано для студентів спеціальностей 073 "Менеджмент", 076 "Підприємництво, торгівля та біржова діяльність".
Міжнародна логістика. Текст лекцій
Keywords: international logistics; managing materials flow; purchasing; supply chain management; transportation; logistics information systems; inventory concepts; warehousing; customer service